KONSERVASI HUTAN LANSKAP KARST MELALUI PEMETAAN DAN IDENTIFIKASI BENTANG ALAM KARST DI DESA BAUMATA - Aisyah Ahmad; Banunaek, Noni (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2025)
The Baumata Groundwater Basin, located in Baumata Village, Taebenu District, Kupang Regency, represents a well-developed karst landscape developed on uplifted limestone. This area is characterized by springs with a total discharge exceeding 150 L/s, and groundwater flow and basin capacity are strongly controlled by the morphology of the limestone lower boundary, limestone thickness, and the distribution of fractures, cavities, and caves. Understanding these hydrogeological and geomorphological characteristics is essential for sustainable water resource management and karst landscape conservation. This study aims to map land cover, analyze karst morphology, and investigate subsurface structures to understand groundwater flow patterns and the interrelation between surface features and underground conduits. The research integrates field surveys, aerial drone mapping, and subsurface investigation using 2D Wenner and VES geoelectric methods. The results indicate that the study area contains 58.68 ha of dense vegetation, including 36.21 ha within the Baumata Conservation/Nature Tourism Park Forest, with 4.23 ha of shrubland. Subsurface interpretations reveal that groundwater flows through cavities, fractures, and cave networks toward the Baumata spring cave, the main discharge point of the system. These findings provide critical insights for conserving the Baumata Tourism Park Forest, protecting the upstream catchment of Baumata Spring, and supporting the development of sustainable geotourism. The study highlights the importance of integrated surface and subsurface mapping in guiding effective karst landscape management and water resource conservation.